Exploring edible landscaping - purpose, plants and places – A review - THAKUR, SHIVANI; KASHYAP, BHARATI; DHIMAN, S.R.; RANA, RICHA; BHANWALA, VIVEK (Journal of Ornamental Horticulture, 2025)
In the wake of increasing urbanisation, modernization and loss of open space, residents in large cities struggle for the space required to establish a traditional food garden. Edible landscaping is a practical food-producing design technique that offers an alternative to conventional agricultural production and urban land use by combining both edible and ornamental plants together in constructed environments. Edibles can be grown on their own or combined with ornamentals to create visually beautiful patterns for existing gardens and yards. Using edibles in landscape design can enhance a garden by providing a unique ornamental component with additional health, aesthetic and economic benefits. Edible crops can assume several landscape functions to create different attractions in each cropping season. Even though edible gardening is focused on food availability at household level, it is also intended to increase interest in the utilization of endemic edible plants and greening of urban spaces to alleviate environmental problems.